Autologous transplantation of adipose-derived stem cells improves functional recovery of skeletal muscle without direct participation in new myofiber formation - Gorecka, Agata (Stem Cell Res Ther, 2018)
BACKGROUND: Skeletal muscle has a remarkable regenerative capacity. However, extensive damage that exceeds the self-regenerative ability of the muscle can lead to irreversible fibrosis, scarring, and significant loss of function. Adipose-derived stem cells (ADSC) are a highly abundant source of progenitor cells that have been previously reported to support the regeneration of various muscle tissues, including striated muscles. The aim of this study was to evaluate the effect of ADSC transplantation on functional skeletal muscle regeneration in an acute injury model. METHODS: Mouse ADSC were isolated from subcutaneous fat tissue and transplanted with a collagen hydrogel into the crushed tibialis anterior muscle of mice. Recovering muscles were analyzed for gene and protein expression by real-time quantitative polymerase chain reaction and immunohistochemistry. The muscle contractility was assessed by myography in an organ bath system. RESULTS: Intramuscular transplantation of ADSC into crushed tibialis anterior muscle leads to an improved muscle regeneration with ADSC residing in the damaged area. We did not observe ADSC differentiation into new muscle fibers or endothelial cells. However, the ADSC-injected muscles had improved contractility in comparison with the collagen-injected controls 28 days post-transplantation. Additionally, an increase in fiber cross-sectional size and in the number of mature fibers with centralized nuclei was observed. CONCLUSIONS: ADSC transplantation into acute damaged skeletal muscle significantly improves functional muscle tissue regeneration without direct participation in muscle fiber formation. Cellular therapy with ADSC represents a novel approach to promote skeletal muscle regeneration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13287-018-0922-1) contains supplementary material, which is available to authorized users.